A influência do comportamento do consumidor na intenção de compra por meio de mobile commerce - Costa, Isadora Lopes da (Universidade Federal Rural do Semi-Árido, 2017)
Due to the advancement of the internet and the use of smartphones by most consumers, there is a growing use of mobile commerce. With this constant development it is necessary an effort of all the involved ones so that the services are in agreement with the behavior of the consumer. The present study aimed to investigate the determinant factors for the decision / intention to buy via mcommerce. Analyze whether the hypotheses of trust, costs, social influence, variety of services, utility, perceived ease, need to test positively affect the adoption of mcommerce purchases. The quantitative research was conducted in the period between July and September/2017, through the application of an electronic questionnaire (Google Forms), obtaining 167 valid respondents, whose data were tabulated and analyzed through the software SPSS and WarpPLS. For the evaluation of the structural model, the partial least squares method - PLS-SEM was used. Among the results of the seven hypotheses tested, six were confirmed, with an average significance level of 0.01 and 45% of explanatory power. Users point out that according to the data obtained, the factors that have the greatest influence on the correlation of the intention of consumption through m-commerce are utility and perceived ease.
Monografia
Keywords: Mobile commerce; Comportamento do consumidor; Dispositivos móveis; Mobile commerce; Consumer behavior; Mobile devices; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO